G416(P) Is Meningococcal B vaccination worth implementing in the Irish population?. (7th April 2014) - Crowley, E; Cunney, R; Nicholson, AJ
Abstract : Aims: Meningococcal B sepsis is a devastating disease with a 5% mortality rate 1 . Effects for survivors include neurological damage, limb amputation and widespread skin necrosis. A compelling case can be made for prevention by immunisation. Since 1997, the multicomponent Meningococcal B vaccine, Bexsero ® has been in development. The European Medicines agency approved the vaccine in November 2012 2 . However, in July 2013 the UK Joint Committee Vaccination and Immunisation (JCVI) stated that they cannot recommend the vaccine to be included for use in the routine immunisation programme in the United Kingdom 3 . No such decision has yet been made on its implementation in the Irish population. Our aim was to assess the disease burden and to ascertain if the Meningococcal B vaccine should be included in the Irish vaccination schedule. Methods: The Health Protection Surveillance Centre (HPSC) publishes an annual report on Meningococcal disease in Ireland 4 . We conducted a retrospective review on surveillance figures over a ten year period, 2002–2012. Subset analysis was performed for a three year period 2009–2011. Results: In total, 1, 867 cases of invasive meningococcal disease (IMD) were notified in Ireland over the ten year period. Serogroup B accounted for 1, 565 (84%). Over the three year period 2009–2011, there were 355 cases of IMD with a crude incidence rate of 2.7/100, 000. Cases ranged from age 1.3 months to 84.6 years (median age 2.4years). Male cases (n = 207) exceeded female cases (n = 147) resulting in a ratio of 1.4:1. There were 12 deaths due to Meningococcal B which corresponded to a case fatality ratio (CFR) of 5%; 4.3%; 2.4% and no deaths due to Meningococcal C. Conclusion: Despite a marked decline in the overall incidence in the past decade, IMD is still an important public health concern. Effective vaccination against Meningococcal B is necessary for the complete prevention and control of Invasive Meningococcal Disease.